Interface shear capacity of facing units of geosynthetic-reinforced segmental retaining walls / Md.Zahidul Islam Bhuiyan - Md. Zahidul Islam , Bhuiyan (2012)
The use of segmental retaining walls (SRWs) is in a period of development at the present time. Today, various types of segmental blocks are extensively used in many geotechnical applications in Malaysia and those blocks are imported from abroad or locally produced under licensed with the agreement of the foreign patent owners. A specially designed and fabricated direct shear apparatus was developed at University of Malaya for full scale laboratory investigation of the innovated block. The developed apparatus was modified by considering the effects of fixed vertical piston on interface shear tests. The experimental works were comprised of three groups of tests. Group 1 was divided into 3 configurations of tests series. The main variable among the test series was stiffness of shear pins. Stiffness of the shear pins varied from zero (no shear pins which allow block to move freely) to very high (steel pins). Another configuration was selected for a medium stiffness of shear pins (plastic pins) falling between the limiting stiffness cases (zero to very high). Frictional performance of hollow I-Block system was examined under three different normal load conditions. Group 2 basically outlined the performance testing of the I-Block system infilled with granular in-fills. As granular in-fills, two types of recycled aggregates were selected and used along with natural aggregates. Recycled aggregates were mainly selected based on the compressive strength of the source waste concretes to investigate the effect of strength property on frictional behavior of recycled aggregates used as in-fillers. Purely frictional capacity of I-Block infilled with recycled aggregates was compared to against those with infilled by fresh aggregates.The tests of Group 3 were configured depending on the flexibility geosynthetic inclusions and granular in-fills. The primary objective of this group was to determine the performance parameters of the new block system with interlocking materials and geosynthetic inclusions. This group represents the potential field conditions of reinforced I-Block walls with proposed interlocking materials. In this group, three types of geosynthetic reinforcements were chosen: a flexible PET-geogrid, a stiff HDPE-geogrid, and a flexible PET-geotextile which are mostly used in Malaysia for GR-SRW constructions. The results of the investigation report that interface shear capacity of the innovated block system greatly was influenced by interlocking mechanisms and interface stiffness. For example, the presence of shear connectors influenced the interface shear capacity depending on the nature of the connectors i.e. rigid or flexible. For the case of granular in-fills, it was found that granular infill definitely increases the interface shear capacity of the blocks compared to empty conditions. The frictional performance of blocks infilled with recycled aggregates is almost equal those with natural aggregates. The results showed that compressive strength of the source waste concretes has a little or no effect on the frictional performance of recycled concrete aggregates used into facing units. Inclusion of a geosynthetic layer at the interface had great influence on interface frictional performance of segmental retaining wall units. It depends on the flexibility of geosynthetic reinforcements as well as block’s interlocking system. The evaluated results report that the angle of friction is greatly influenced by the inclusion’s characteristics i.e. flexibility or rigidity than aggregate types.